2006
DOI: 10.1002/14651858.cd005534.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen therapy in the pre-hospital setting for acute exacerbations of chronic obstructive pulmonary disease

Abstract: Oxygen therapy in the pre-hospital setting for acute exacerbations of chronic obstructive pulmonary disease (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…A 2006 Cochrane review of oxygen therapy for COPD in the prehospital setting found no relevant randomised studies but the paper by Austin et al 51 in 2010 has shown a reduced mortality in patients with COPD in prehospital care who were managed with titrated oxygen to achieve a target saturation of 88–92% compared with high-concentration oxygen therapy (RR 0.22) 445…”
Section: Section 9: Emergency Use Of Oxygen In Ambulances Community mentioning
confidence: 99%
“…A 2006 Cochrane review of oxygen therapy for COPD in the prehospital setting found no relevant randomised studies but the paper by Austin et al 51 in 2010 has shown a reduced mortality in patients with COPD in prehospital care who were managed with titrated oxygen to achieve a target saturation of 88–92% compared with high-concentration oxygen therapy (RR 0.22) 445…”
Section: Section 9: Emergency Use Of Oxygen In Ambulances Community mentioning
confidence: 99%
“…[12][13][14] Oxygen is also recommended for compromised patients with chronic obstructive pulmonary diseases because studies have shown that the short period of higher oxygen saturation will not result in adverse ventilatory depression of the patient. 15,16 One surprising aspect identified during the course of the investigation was that this was the very first time many students had physically operated the supplemental oxygen equipment. Most had only received training in nitrous oxide analgesia during their second year and had not yet interacted with an actual patient requiring nitrous oxide/oxygen during a dental procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A report on prehospital thrombolysis showed a reduction in time to thrombolysis, but limited evidence of its safety or on its long‐term outcomes 4 . Finally, a report on the use of oxygen for patients with chronic obstructive pulmonary disease noted that, of 741 abstracts reviewed, only two were of randomised controlled trials, both of which were ongoing and lacking outcome data 5 . Much of the literature lacks an understanding of how its findings apply in the uncontrolled environment that characterises prehospital care.…”
Section: Relating Evidence To Practice In Uncontrolled Environmentsmentioning
confidence: 99%